Extensive diet-induced atherosclerosis in scavenger receptor class B type 1-deficient mice is associated with substantial leukocytosis and elevated vascular cell adhesion molecule-1 expression in coronary artery endothelium - Fuller, Mark T.; Dadoo, Omid; Xiong, Ting; Chivukula, Pardh; MacDonald, Melissa E.; Lee, Samuel K.; Austin, Richard C.; Igdoura, Suleiman A.; Trigatti, Bernardo L. (Frontiers in Physiology, 2023)
High levels of low density lipoprotein (LDL) cholesterol and low levels of high density lipoprotein (HDL) cholesterol are risk factors for cardiovascular disease. Mice that lack genes involved in the clearance of LDL from the bloodstream, such as the LDL receptor and apolipoprotein E, are widely used models of experimental atherosclerosis. Conversely, mice that lack the HDL receptor, scavenger receptor class B type I, and therefore have disrupted HDL functionality, also develop diet-inducible atherosclerosis but are a seldom-used disease model. In this study, we compared atherosclerosis and associated phenotypes in scavenger receptor class B type I knockout mice with those of wild type, LDL receptor knockout, and apolipoprotein E knockout mice after 20 weeks of being fed an atherogenic diet containing sodium cholate. We found that while scavenger receptor class B type I knockout mice had substantially lower plasma cholesterol than LDL receptor and apolipoprotein E knockout mice, they developed atherosclerotic plaques with similar sizes and compositions in their aortic sinuses, and more extensive atherosclerosis in their descending aortas and coronary arteries. This was associated with elevated tumor necrosis factor alpha levels in scavenger receptor class B type I knockout mice compared to wild type and LDL receptor knockout mice, and lymphocytosis, monocytosis, and elevated vascular cell adhesion molecule expression in coronary artery endothelial cells compared to the other mice examined. We conclude that extensive atherosclerosis in arteries that are not generally susceptible to atherosclerosis in scavenger receptor class B type I knockout mice is driven by factors in addition to hypercholesterolemia, including inflammation, dysregulation of the immune system and increased sensitivity of endothelial cells in arteries that are normally resistant to atherosclerosis. Scavenger receptor class B type I knockout mice fed a cholate containing atherogenic diet may prove to be a useful model to study mechanisms of atherosclerosis and evaluate treatments that rely on intact LDL clearance pathways.